Existentialism of Main Characters in the Movie: Final Destination 5 - Ni Kadek Wina Valentina; Putu Weddha Savitri; Yana Qomariana (Pusat riset dan Inovasi Nasional, 2025)
This study examines the portrayal of existentialist principles and characterization in Final Destination 5 (2011), directed by Steven Quale. The research aims to identify the methods of characterization used for the five main characters and explore how Sartrean existentialism is reflected in their struggles. Using a qualitative approach, the study applies Kenney’s method of characterization and Sartre’s existentialist framework to analyze key scenes, dialogues, and character interactions. Data was collected through repeated viewings of the film, with critical moments transcribed and categorized based on characterization methods and existential principles. The findings reveal that Final Destination 5 employs a mixed method, with the dramatic method being the most dominant, supplemented by character on other characters and contextual methods to develop psychologically complex main characters. Existentialist principles emerge strongly, particularly the idea that